2022
DOI: 10.3390/cells11030394
|View full text |Cite
|
Sign up to set email alerts
|

Causes of and Molecular Targets for the Treatment of Intervertebral Disc Degeneration: A Review

Abstract: Intervertebral disc degeneration (IVDD) is a pathological condition that can lead to intractable back pain or secondary neurological deficits. There is no fundamental cure for this condition, and current treatments focus on alleviating symptoms indirectly. Numerous studies have been performed to date, and the major strategy for all treatments of IVDD is to prevent cell loss due to programmed or regulated cell death. Accumulating evidence suggests that several types of cell death other than apoptosis, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
67
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 146 publications
(302 reference statements)
0
67
0
Order By: Relevance
“…It is a programmed cell death, also known as inflammatory necrosis, closely related to inflammation, immunity, and apoptosis [ 11 ]. Various studies have shown that pyroptosis plays a crucial role in IDD [ 12 , 13 ]. When NP cells (NPCs) undergo pyroptosis, the main manifestations are raised inflammatory factors, NLRP3, caspase-1, and other genes [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is a programmed cell death, also known as inflammatory necrosis, closely related to inflammation, immunity, and apoptosis [ 11 ]. Various studies have shown that pyroptosis plays a crucial role in IDD [ 12 , 13 ]. When NP cells (NPCs) undergo pyroptosis, the main manifestations are raised inflammatory factors, NLRP3, caspase-1, and other genes [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The delicate balance between catabolism and anabolism is lost in IVD, and a series of degradation processes start and are facilitated by numerous factors (e.g., genetic and environmental changes) ( Ravichandran et al, 2022 ). There are some critical pathological changes during IVDD, consisting of abnormal synthesis and degradation of ECM, cellular senescence and death, increased angiogenesis and innervation, aging of AF, as well as calcification of CEP ( Ohnishi et al, 2022 ; Wang et al, 2020 ).…”
Section: Intervertebral Disc and Intervertebral Disc Degenerationmentioning
confidence: 99%
“…When NCs are gradually lost, and the dialogue with NPS cells ends, IVDD occurs ( Erwin et al, 2006 ). At the early stage of IVDD, the productions of aggrecan and type II collagen are inhibited, the water of hyaluronic acid polymerized into proteoglycan is lost, whereas the productions of type I collagen, fibronectin, and other proteoglycans are facilitated ( Ohnishi et al, 2022 ; Yee et al, 2016 ). This finding is correlated with an upregulated expression of matrix-degrading proteins (e.g., MMPs and ADAMTS).…”
Section: Intervertebral Disc and Intervertebral Disc Degenerationmentioning
confidence: 99%
“…Some IVDD patients benefit from conservative care, which includes physiotherapy, oral analgesics, vitamins, exercise, heat, cold, corsetry, acupuncture, radio frequency/shock waves, and varying intensities of massage [ 204 , 205 , 207 ]. However, the condition worsens for some patients or frequently recurs [ 208 ].…”
Section: Current Treatment Approaches For Ivddmentioning
confidence: 99%